Masalah Penyediaan Tanah Dalam Hubungan Dengan Pengembangan Kota - Budhy Tjahjati S Soegijoko (Journal of Regional and City Planning, 1995)
The growing demand on land, while the supply is limited, is the reason for the sharp increase in the value of land in urban area. On the one hand, the provision of urban infrastructure services using land as the bases of activities are forced to fulfill the ever growing demand of human needs. On the other hand, the improvements of infrastructure services are responsibility of the government.The accumulation of that condition resulted in the degradation of the urban environmental quality, such as the spread of slum area, the increase in traffic congestion, and poor utility services.